Determination of Strength Improvements in the Acacia Hybrid Through the Combination of Age Groups at the Air-Dry Conditioning Stage - Fanthy Moola, Malek; Gaddafi, Ismaili; Noor Azland, Jaimudin; Meekiong, Kalu; Mohd Effendi, Wasli; Ahmad Fadzil, Jobli; Mohamad Zain, Hashim; Ahmad Nurfaidhi, Rizalman; Nur Syahina, Yahya; Semilan, Ripot (MDPI, 2025)
Acacia hybrid is an important plantation species in Malaysia, but its use in structural applications is still limited due to the lack of comprehensive data on its engineering properties. This study evaluated the physical and mechanical properties of laminated or glulam Acacia hybrid timber in an air-dried condition for three age group combinations (7//10, 10//13, and 7//13 years old) to determine the optimal combination for structural applications. The results showed that the 10//13-year-old combination had the best mechanical performance, along with the highest basis density (0.7099 g/cm3), highest modulus of elasticity (MOE) (16,335.6 N/mm2 ), and highest parallel compressive strength (56.998 N/mm2 ), while the 7//10-year-old combination showed the highest moisture content (14.94%) and highest perpendicular compressive strength (8.9256 N/mm2 ). This study demonstrated that the combination of juvenile wood (7 years old) with mature wood (10 or 13 years old) increased strength by up to 43.06%, thus optimising the potential of Acacia hybrid in the construction industry. All combinations meet SG5 standards, with the 10//13-year-old combination recommended as the best choice for high-performance applications of glulam products.